Global patterns of national climate policies: analyzing 171 country portfolios on climate policy integration - Schmidt, Nicole; Fleig, Andreas (Environmental science & policy, 2018)
Over the last decades, a growing number of countries around the world adopted policies towards climate change. However, apart from the remarkable increase in legislative activity, we know little about the composition of country portfolios on climate policy and whether those rely mainly on specific climate policies or the integration of climate objectives across domains. Research on policy integration is often bound by a dearth of suitable data and has to rely on small-n comparative case study designs or a certain type of policy when investigating these phenomena. Our paper addresses this gap by drawing on the Climate Change Laws of the World database for national climate legislation across eight policy categories. Hereby, we systematically assess how climate-related policies have developed over the last 27 years and across 171 countries. The analysis shows that since 1990, the scope of country portfolios has risen considerably. This increase started somewhat slowly in the 1990s but accelerated afterwards across all categories, albeit at different times and to varying degrees of coverage. In particular, climate policies on energy demand and supply as well as administrative arrangements are widespread. Our findings suggest that efforts at CPI were more common in the energy than the transportation domain. The focus of climate specific categories, i.e. no efforts at CPI, were ‘administrative arrangements’, and, albeit to a much lesser extent, policies addressing carbon pricing. With respect to future climate action, the results of our cross-country analysis are two-fold. On the one hand, it is reasonable to assume that countries not having enacted policies in the most commonly addressed categories will soon follow suit. On the other hand, transportation and carbon pricing, specifically, are policy areas that are least addressed in our sample and represent an area where much is yet to be uncovered.
Gesehen am 31.01.2018